Mathematical Modeling Of Simultaneous Removal Of So2 And No Using Sorbent Synthesized From Ash - Yew, Henry Foo Chee (2010)
Mathematical modeling and applied analysis combine the strengths of applied mathematics, kinetic studies and numerical analysis to derive, analyze and solve mathematical models of complex problems. These techniques were used in this study for solving a complex heterogeneous gas-solid reaction for the removal of sulfur dioxide (SO2) and nitrogen oxide (NO) in flue gas using siliceous sorbent. Generally, its complexities encompassed three level of studies; macro-, meso- and micro-scopic kinetic analysis. Model 1 was developed based on a global reaction rate between SO2 and coal fly ash/CaO/CaSO4 (dry sorbent).